Digitalisasi Sistem Pelaporan dan Pengawasan untuk Hakim Pengawas Pengamat - Sofia Nur Azizah Samsi (Jurnal Hukum Lex Generalis, 2025)
Supervisory and Observing Judges (Wasmat) play an important role in ensuring that criminal sentence implementation runs fairly and respects human rights. However, the current manual supervision system is often ineffective, poorly coordinated and lacks accountability. Limited human resources and infrastructure also make it difficult to carry out transparent supervision. Therefore, digitalizing the supervision process is needed to make it more efficient and aligned with developments in legal technology. This study uses a normative juridical method by reviewing regulations such as the Criminal Procedure Code (KUHAP), the Correctional Law and Supreme Court Regulations, as well as related legal literature. The analysis was conducted qualitatively to find solutions for strengthening the supervision system through digital technology. The results show that digitalization is essential to improve the effectiveness and accountability of supervision. A digital system can make the process more measurable and transparent, although challenges remain in legal frameworks, technological infrastructure and officials’ digital literacy. Regulatory reforms, stronger information systems and enhanced digital skills are needed to ensure that supervision becomes more effective and fair.